Impact of regular physical activity on blood glucose control and cardiovascular risk factors in adolescents with type 2 diabetes mellitus – a multicenter study of 578 patients from 225 centres. Issue 3 (2nd June 2014) - Herbst, A; Kapellen, T; Schober, E; Graf, C; Meissner, T; Holl, RW; for the DPV‐Science‐Initiative
Abstract Introduction Regular physical activity (RPA) is a major therapeutic recommendation in children and adolescents with type 2 diabetes mellitus (T2DM). We evaluated the association between frequency of RPA and metabolic control, cardiovascular risk factors, and treatment regimes. Methods The Pediatric Quality Initiative (DPV), including data from 225 centers in Germany and Austria, provided anonymous data of 578 patients (10–20 yr; mean 15.7 ± 2.1 yr; 61.9% girls) with T2DM. Patients were grouped by the frequency of their self‐reported RPA per week: RPA 0, none; RPA 1, 1–2×/wk; RPA 2, >2×/wk. Results The frequency of RPA ranged from 0 to 9×/wk (mean 1.1×/wk ±1.5). 55.7% of the patients reported no RPA (58.1% of the girls). Hemoglobin A1c (HbA1c) differed significantly among RPA groups (p < 0.002), being approximately 0.8 percentage points lower in RPA 2 compared to RPA 0. Body mass index (BMI‐SDS) was higher in the groups with less frequent RPA (p < 0.00001). Multiple regression analysis revealed a negative association between RPA and HbA1c (p < 0.0001) and between RPA and BMI‐SDS (p < 0.01). The association between RPA and high density lipoprotein (HDL)‐cholesterol was positive (p < 0.05), while there was no association to total cholesterol, low density lipoprotein (LDL)‐cholesterol or triglycerides. Approximately 80% of the patients received pharmacological treatment (oral antidiabetic drugs and/or insulin) without differences between RPA groups. Conclusion More than half of the adolescents with T2DM did not perform RPA. Increasing physical activity was associated with a lower HbA1c, a lower BMI‐SDS, a higher HDL‐cholesterol, but not with a difference in treatment regime. These results suggest that regular exercise is a justified therapeutic recommendation for children and adolescents with T2DM.